Testing variations between starters and substitute players in terms of total distance, high-speed running, and sprinting distance: a descriptive study on professional male soccer players - Janusiak, M.; Silva, A. F.; Silva, R.; Kosendiak, A.; Bogdanski, B.; Smoter, M.; Praça, G.; Clemente, F. M. (Biology of Sport, 2024)
The purpose of this study was three-fold: (i) to compare total distance, high-speed running (HSR) distance, and sprint distance covered per 5-minute epoch by players acting as both starters and substitutes; (ii) to compare the locomotor demands between the moments the players entered the match (45-60, 60-75 and 75-90 minutes); and (iii) to compare the locomotor demands of the players between the variations of the withinand between-playing positions. Twenty-one male professional soccer players competing in the Professional Premier League of one of the European countries were observed over sixteen official matches. The players were monitored during all matches using a Global Navigation Satellite System. The measures collected were total distance (TD; m), distance in HSR, sprint distance, HSR, and sprint counts. Considering the comparisons between the splits over the second half of match play, a significant difference between the starters and the substitutes was observed only for sprint distance in the 90-95 minute split (Z = -2.023; p = 0.043). Moreover, no substantial differences were found between the moment the substitute player entered the match regarding total distance (H = 2.650; p = 0.266), HSR distance (H = 1.738; p = 0.419), and sprint distance (H = 0.048; p = 0.976). However, the comparison of between-playing positions revealed considerable differences in total distance (H = 29.246; p < 0.001), and HSR distance (H = 12.153; p = 0.002) covered by the players acting as starters. In contrast, for substitute players, such differences were reported in HSR distance (H = 27.892; p < 0.001) and sprint distance (H = 15.879; p < 0.001). In conclusion, this study suggests that acting as a starter or a substitute does not significantly affect the intensity of effort except during the last periods of match play. However, the contextual factor of performing in a specific playing position plays a significant role both forstarters and substitutes.